Echocardiographic markers of dyssynchrony as predictors of super-response to cardiac resynchronisation therapy – a pilot study - Kuznetsov, V. A. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Some patients with congestive heart failure have greater improvement of cardiac remodelling after cardiac resynchronisation therapy (CRT) and they are identified as super-responders (SRs). It remains unclear if echocardiographic markers of dyssynchrony could accuratelly predict super-response to CRT. The aim of this study is to evaluate potential echocardiographic predictors associated with super-response to CRT. METHODS: Fifthy nine CRT patients (mean age 52.9 ± 9.0 years, 88% men) with congestive heart failure (54% ischaemic and 46% non-ischaemic aetiology) II-IV NYHA functional class were enrolled. To assess mechanical dyssynchrony we evaluated interventricular mechanical delay, the maximum delay between peak systolic velocities of the septal and posterior walls of left ventricle, duration of left ventricular pre-ejection period (LVPEP), left ventricular and interventricular dyssynchrony by tissue Doppler imaging and systolic dyssynchrony index by 3D echocardiography. After six months the patients were assessed for response and classified as SRs (reduction in left ventricular end-systolic volume (LVESV) ≥30%, n = 20) and non-SRs (reduction in LVESV < 30%, n = 39) and baseline data were analyzed to identify the predictors. RESULTS: Both groups demonstrated significant improvement in NYHA functional class, increase in left ventricular ejection fraction and reduction in LVESV. All parameters of mechanical dyssynchrony at baseline were significantly higher in SR group. Multiple logistic regression analysis showed that LVPEP (HR 1.031; 95% CI 1.007–1.055; p = 0.011) was an independent predictor for CRT super-response. In ROC curve analysis LVPEP with a cut-off value of 147 ms demonstrated 73.7% sensitivity and 75% specificity (AUC = 0.753; p = 0.002) for the prediction of super-response to CRT. CONCLUSION: Greater mechanical dyssynchrony is associated with super-response to CRT in patients with congestive heart failure. It is probable that an LVPEP > 147 ms can be used as independent predictor of super-response.